Comparison of Anisotropic Analytical Algorithm and Acuros XB Calculation Algorithms on Intensity-modulated Radiotherapy and Volumetric Modulated Arc Therapy Techniques for Nasal Cavity and Paranasal Sinus Tumors: Effects on Integral Radiation Dose - Çakır, Aydın; Akgün, Züleyha (KARE PUBL, 2019)
OBJECTIVE This study aims to investigate the dosimetric effects of Acuros XB (AXB) and Anisotropic Analytical algorithms (AAA) on intensity-modulated radiotherapy (IMRT) and volumetric modulated arc therapy (VMAT) techniques for nasal cavity and paranasal sinus tumors. METHODS This study included 10 patients with the nasal cavity and paranasal sinus tumors, and 7-field non-coplanar IMRT plan and VMAT plans were generated with 6-MV photon beams specially selected for each patient anatomy. The effects on planning target volume (PTV) and organ-at-risk (OAR) were evaluated using AXB and AAA in each treatment technique to compare the accuracy of the calculation. RESULTS Conformity Index (CI) values for PTV were found to be 1.02 +/- 0.02 and 1.03 +/- 0.03 for VMAT(AAA) and VMAT(AXB) plans, respectively and 1.18 +/- 0.03 and 1.20 +/- 0.02 for IMRTAAA and IMRTAXB plans, respectively. Regarding heterogeneity index (HI) values, VMAT(AAA) and VMA(AXB) plans (0.025 +/- 0.02; 0.029 +/- 0.02) were found to have better HI values than IMRTAAA and IMRTAXB plans (0.246 +/- 0.02; 0.335 +/- 0.03). Depending on the technique and algorithm used, a dose difference of 4%-14% was detected between PTV Drain values. CONCLUSION The selection of AXB algorithm treatment regions with high tissue heterogeneity will give more accurate dose calculation results for PTV and healthy tissues.
Keywords: Anisotropic analytical algorithm; Acuros XB; nasal cavity; radiotherapy for paranasal sinus; integral dose